2020
DOI: 10.1186/s13195-020-00635-0
|View full text |Cite
|
Sign up to set email alerts
|

Partial reduction of amyloid β production by β-secretase inhibitors does not decrease synaptic transmission

Abstract: Background: Alzheimer's disease (AD) is the most common form of age-related neurodegenerative diseases. Cerebral deposition of Aβ peptides, especially Aβ42, is considered the major neuropathological hallmark of AD and the putative cause of AD-related neurotoxicity. Aβ peptides are produced by sequential proteolytic processing of APP, with β-secretase (BACE) being the initiating enzyme. Therefore, BACE has been considered an attractive therapeutic target in AD research and several BACE inhibitors have been test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
(61 reference statements)
1
21
0
Order By: Relevance
“…Concordantly, recent studies have suggested that the negative effect of BACE inhibitors on cognition might be independent of the presence of brain amyloid and appears reversible after compound washout [41]. Some authors have suggested that lower BACE inhibition may have potential in future trials [39,42,43].…”
Section: Discussionmentioning
confidence: 97%
“…Concordantly, recent studies have suggested that the negative effect of BACE inhibitors on cognition might be independent of the presence of brain amyloid and appears reversible after compound washout [41]. Some authors have suggested that lower BACE inhibition may have potential in future trials [39,42,43].…”
Section: Discussionmentioning
confidence: 97%
“… 10 A recent report implies that inhibition of less than 50% of Aβ might preserve neuronal signalling because the APP family plays an important role in synaptic plasticity underlying learning and memory. 52 Thus, we designed the clinical trial for PSEN1-AD with the expectation that bromocriptine will become a candidate as a molecularly targeted drug for AD, and especially for PSEN1-AD.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major focuses of drug discovery efforts in the AD area has been the development of drug candidates to regulate abnormal Aβ aggregation. Several synthetic drugs have been evaluated in clinical trials, including LY2886721 [ 113 ], AN1792 [ 114 ] and verubecestat [ 115 ], along with monoclonal antibody drugs such as donanemab, which targets Aβ 3–42 [ 116 ] and aducanumab (BIIB037), which targets a conformational epitope found on Aβ [ 117 ]. However, none of them have been successful in the treatment of AD.…”
Section: Neuroprotective Mechanisms Of Natural Products For Admentioning
confidence: 99%